Timing of the first cannulation and survival of arteriovenous grafts in hemodialysis patients: a multicenter retrospective cohort study. Issue 1 (1st January 2021) - Lin, Su-Ju; Chang, Shu-Chen; Tung, Chun-Wu; Hsu, Yung-Chien; Shih, Ya-Hsueh; Wu, Yi-Ling; Chou, Tse-Chih; Lin, Chun-Liang
Abstract: Arteriovenous graft (AVG) is an important vascular access route in hemodialysis patients. The optimal waiting time between AVG creation and the first cannulation is still undetermined, therefore the current study investigated the association between ideal timing for cannulation and AVG survival. This retrospective cohort study used data from the Taiwan National Health Insurance Database, which included 6, 493 hemodialysis patients with AVGs between July 1 st 2008 and June 30 th 2012. The waiting cannulation time was defined as the time from the date of shunt creation to the first successful cannulation. Patients were categorized according to the waiting cannulation time of their AVGs as follows: ≤30 days, between 31 and 90 days, between 91 and 180 days, and >180 days. The primary outcome was functional cumulative survival, measured as the time from the first cannulation to shunt abandonment. The AVGs which were cannulated between 31 and 90 days (reference group) after construction had significantly superior functional cumulative survival compared with those cannulated ≤30 days (adjusted HR = 1.651 with 95% CI 1.482–1.839; p < 0.0001) and >180 days (adjusted HR = 1.197 with 95% CI 1.012–1.417; p = 0.0363) after construction. An analysis of the hazard ratios in patients with different demographic characteristics, revealed that the functional cumulative survival of AVGs in most groups was better when they received cannulation >30 days after construction. Consequently, in order to achieve the best long-term survival, AVGs should be cannulated at least 1 month after construction, but you should avoid waiting for >3 months.